Sowiecko-polskie relacje wojskowo-polityczne na Wileńszczyźnie w latach II wojny światowej - Wołkonowski, Jarosław (Przegląd Wschodnioeuropejski, 2023)
The Polish underground in the Wilno region made three attempts to reach an agreement with the Soviet occupier, who was a major player in the anti-Nazi coalition. The question of Poland’s borders after World War II was a key hurdle to the Soviet-Polish agreement. The Polish government-in-exile could not maintain diplomatic relations with the Soviet Union during the decisive period, which made it difficult to find local agreements of the Polish underground in the Wilno region with “an ally of our allies”. In its relations with the Polish underground in the Wilno region, the Soviet command hypocritically used the Soviet- -Polish talks to accomplish its goal – the destruction of the Polish underground.